2018
DOI: 10.1002/btpr.2738
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of two novel purple naphthoquinone pigments concomitant with the bioactive red bikaverin and derivates thereof produced by Fusarium oxysporum

Abstract: Filamentous fungi have gained growing interest as sources of diverse pigmented secondary metabolites. Some specific polyketides from Ascomycetous species have demonstrated a wide range of industrial applications in food, cosmetic, textile, and in the design of pharmaceutical products. The formulation of recipes containing fungal polyketides has increased over recent years. Fusarium strains were proven useful to mankind in a variety of technologies. Nevertheless, there is still need of new isolates of Fusarium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 52 publications
(144 reference statements)
2
40
0
Order By: Relevance
“…Studies have reported pigments such as bikaverin, nor-bikaverin, fusarubins, some naphthoquinone(8-O-methybostrycoidin, 8-O-methylfusarubin, 8-O-methylnectriafurone, 8-O-methyl-13-hydroxynorjavanicin, 8-O-methylanhydrofusarubinlactol, and 13-hydroxynorjavanicin), and a novel isoquinoline-type, pigment 2-(4-((3E,5E)-14-aminotetradeca-3,5-dienyloxy)butyl)-1,2,3,4tetrahydroisoquinolin-4-ol (ATDBTHIQN), from Fusarium fujikuroi (formerly known as Fusarium moniliforme) (Figure 2) [25,63,65]. Similarly, differently colored naphthoquinones [bostrycoidin, 9-O-methylfusarubin, 5-O-methyljavanicin, 8-O-methylbostrycoidin, 1,4-naphthalenedione-3,8dihydroxy-5,7-dimethoxy-2-(2-oxopropyl), 5-O-methylsolaniol, and 9-O-methylanhydrofusarubin], two anthraquinones compounds [2-acetyl-3,8-dihydroxy-6-methoxy anthraquinone and 2-(1-hydroxyethyl)-3,8-dihydroxy-6-methoxy anthraquinone], and polyketide pigment (bikaverin) were reported from Fusarium oxysporum(Figure 2)[25,47,64,67]. Another species of Fusarium, Fusarium graminearum, has been found to produce a variety of pigments such as 5-deoxybostrycoidin anthrone, 6-O-dimethyl-5deoxybostrycoidin anthrone, purpurfusarin, 6-O-demethyl-5-deoxybostrycoidin, 5-deoxybostrycoidin, and aurofusarin (Figure 2)[25,64,66,121].…”
mentioning
confidence: 99%
“…Studies have reported pigments such as bikaverin, nor-bikaverin, fusarubins, some naphthoquinone(8-O-methybostrycoidin, 8-O-methylfusarubin, 8-O-methylnectriafurone, 8-O-methyl-13-hydroxynorjavanicin, 8-O-methylanhydrofusarubinlactol, and 13-hydroxynorjavanicin), and a novel isoquinoline-type, pigment 2-(4-((3E,5E)-14-aminotetradeca-3,5-dienyloxy)butyl)-1,2,3,4tetrahydroisoquinolin-4-ol (ATDBTHIQN), from Fusarium fujikuroi (formerly known as Fusarium moniliforme) (Figure 2) [25,63,65]. Similarly, differently colored naphthoquinones [bostrycoidin, 9-O-methylfusarubin, 5-O-methyljavanicin, 8-O-methylbostrycoidin, 1,4-naphthalenedione-3,8dihydroxy-5,7-dimethoxy-2-(2-oxopropyl), 5-O-methylsolaniol, and 9-O-methylanhydrofusarubin], two anthraquinones compounds [2-acetyl-3,8-dihydroxy-6-methoxy anthraquinone and 2-(1-hydroxyethyl)-3,8-dihydroxy-6-methoxy anthraquinone], and polyketide pigment (bikaverin) were reported from Fusarium oxysporum(Figure 2)[25,47,64,67]. Another species of Fusarium, Fusarium graminearum, has been found to produce a variety of pigments such as 5-deoxybostrycoidin anthrone, 6-O-dimethyl-5deoxybostrycoidin anthrone, purpurfusarin, 6-O-demethyl-5-deoxybostrycoidin, 5-deoxybostrycoidin, and aurofusarin (Figure 2)[25,64,66,121].…”
mentioning
confidence: 99%
“…Red carotenoids from plants are quite frequent. Natural carotenoids exhibit different health benefits confirmed by recent studies: strong antioxidant property, anti‐inflammatory effects, anti‐obesity, anticancer, prevention of cardiovascular diseases, of night blindness, and of liver fibrosis, etc …”
Section: Introductionmentioning
confidence: 98%
“…These biomolecules which are derived from isoprenoids, represent a diverse class of phenolic compounds . The three main groups of naturally occurring quinones are benzoquinones, naphthoquinone, and anthraquinones . These natural dyes produce yellow, orange, red, or reddish‐brown to purple colors.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations